2015
DOI: 10.1039/c5nr02903a
|View full text |Cite
|
Sign up to set email alerts
|

Perylenetetracarboxylic anhydride as a precursor of fluorescent carbon nanoonion rings

Abstract: Royal Society of ChemistryGarcía Baldoví, H.; Víctor, VM.; Herance Camacho, JR.; Alvaro Rodríguez, MM.; García Gómez, H. (2015). Perylenetetracarboxylic anhydride as a precursor of fluorescent carbon nanoonion rings. Nanoscale. 7(29)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The height of these C-NORs was determined by AFM images that show that C-NORs are at objects with a size of 2.5 nm. 31 No differences in the morphology and dimensions between C-NOR and C-NOR(Eu) could be observed and ICP-OES determined the total absence of Eu in the C-NOR(Eu) sample. However, FT-IR spectroscopy does show that the carboxylic functional groups of C-NOR(Eu) have undergone a higher level of esterication of PTA carboxylic anhydride groups when Eu 3+ is present in the thermolysis as compared to C-NOR, in accordance of the role of Eu 3+ as esterication catalyst.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The height of these C-NORs was determined by AFM images that show that C-NORs are at objects with a size of 2.5 nm. 31 No differences in the morphology and dimensions between C-NOR and C-NOR(Eu) could be observed and ICP-OES determined the total absence of Eu in the C-NOR(Eu) sample. However, FT-IR spectroscopy does show that the carboxylic functional groups of C-NOR(Eu) have undergone a higher level of esterication of PTA carboxylic anhydride groups when Eu 3+ is present in the thermolysis as compared to C-NOR, in accordance of the role of Eu 3+ as esterication catalyst.…”
Section: Resultsmentioning
confidence: 94%
“…Regarding to photoluminescence properties, it was found that C-NOR and C-NOR(Eu) have high uorescence emission intensity that depends on the excitation wavelength. 31 The presence of Eu 3+ in the thermolysis favors the formation of C-NOR and also increases somewhat the emission intensity band of C-NORs despite the fact that this rare earth metal ion was absent in the resulting nanoparticle. C-NOR and C-NOR(Eu) are highly emissive nanoparticles with an estimated photoluminescence quantum yield about 0.47 and 0.49, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations